Supernumerary Teeth: A Retrospective Cross-Sectional Study from Palestine - Naji Ziad Arandi; Ameed Abu-Ali; Shockry Mustafa (Association of Support to Oral Health Research (APESB), 2022)
Objective: To investigate the prevalence and characteristics of supernumerary teeth among patients attending the students' dental clinics at the Faculty of Dentistry of the Arab American University, Jenin, Palestine. Material and Methods: This is a descriptive, cross-sectional, retrospective study of 1970 digital panoramic radiographs of patients, age ranging between 12 and 50 years. The radiographs and dental records were reviewed for supernumerary teeth. For each patient with supernumerary teeth, were recorded the demographic variables, number, location, eruption status, type, and morphology, the developmental stages. Descriptive statistics were performed and results were tabulated. Results: Supernumerary teeth were detected in 17 subjects (0.86%), of which 13 were males and 4 were females with a male to female ratio of 3.25:1. Of the 17 patients, 64.7% had one supernumerary tooth while the others had two. The majority (78.3%) of the supernumeraries were located in the maxilla. Around 56.5% of the supernumeraries found in this study were located in the premaxilla. Half of the supernumeraries (52.2%) were erupted, and 47.8% were impacted. Mesiodens was the most frequently seen supernumerary teeth followed by distomolars and premolars. Most of the supernumeraries were fully developed, while 21.7% displayed only crown formation. Conclusion: The prevalence of supernumerary teeth in the study sample was found to be 0.86% and the most frequent type was mesiodens. Supplemental morphology was found to be the most common form of supernumerary teeth.